Compliance with the 24-hour movement guidelines and weight status: results from 40,970 adolescents - Su, Yang (Frontiers in Public Health, 2025)
BackgroundChildhood obesity, which has been associated to heart disease, metabolic syndrome and disorders such as feelings of worry and sadness in children is one of the prominent obstacles for the health of the general population in the recent decades. A great deal of research shown the connection between meeting the 24-hour movement guidelines and weight status in young people. The purpose of this study is to find the correlation between compliance with the 24-hour movement guidelines and weight status in a large collection of U.S. teenagers, and to examine whether these connections vary by sex, age, or ethnicity/race.MethodsThe study was gathered from the Youth Risk Behaviour Survey (YRBS) conducted in 2017, 2019, and 2021, the final analysis used a total of 40,970 participants aged 14–17 years. The study used logistic regression analysis to estimate the correlation between adherent to the 24-hour movement guidelines (independent) and weight status (dependent) while adjusting for sex, age, race/ethnicity, grade, eating habits, cigarette use, alcohol drinking, perception of weight, weight loss, sports team participation, and year of data acquisition. For statistical significance, a p-value <0.05was used.ResultsParticipators who not meeting any guidelines (OR = 1.38, CI = 1.20–1.58, p < 0.001), 1 guideline (OR = 1.42, CI = 1.28–1.58, p < 0.001), and 2 guidelines (OR = 1.18, CI = 1.20–1.58, p < 0.001) were more associated with worse weight status, compared with those who met the 3 guideline. For boys, who did not meet any of the guidelines (OR = 1.63, CI = 1.37–1.93, p < 0.001), 1 guideline (OR = 1.49, CI = 1.31–1.70, p < 0.001), and 2 guidelines (OR = 1.16, CI = 1.00–1.34, p = 0.048) were correlated with unfavourable weight status compared with who met all guidelines were more associated. The disaggregated results for gender, age, race, and ethnic group shows that the impact of not adhering to movement guidelines is more pronounced in boys than in girls, each age group demonstrates a trend where not meeting guidelines correlates with poorer weight status, White and Hispanic/Latino participants exhibit stronger negative outcomes from poor guideline adherence compared to other groups.ConclusionThis research suggests that meeting the 24-hour movement guidelines can significantly aid in averting weight-related problems among U.S. adolescents, with pronounced differences across sex, age, race/ethnicity subgroups. To validate these preliminary findings, future research should employ longitudinal designs to examine the differences among various age groups, sexes, and races, and to determine if promoting adherence to these movement guidelines effectively mitigates weight-related issues during adolescence.